Penerapan Etika Pelayanan Publik Dalam Meningkatkan Kualitas Pelayanan Di Birokrasi Pemerintah Daerah - Mozin, Sri Yulianty (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Public service ethics is a fundamental aspect in shaping the quality image of local government bureaucracy. This study aims to examine how the application of public service ethics affects service quality within local government institutions. The method used in this study is a qualitative approach with case studies in several regional government agencies in Indonesia. The results show that ethical principles such as honesty, responsibility, transparency, and concern for the public positively correlate with increased public satisfaction and service efficiency. The study also reveals that weaknesses in ethics implementation stem from lack of supervision, limited understanding of ethical values among officials, and inadequate professional ethics training. This research recommends the systemic internalization of ethical values and strengthening of an integrity-based organizational culture as strategies to improve the quality of public service.